Vessel feature changes as a tool for detecting annual rings in tropical trees - Ohashi, Shinta; Okada, Naoki; Abdul Azim, Amir Affan; Siripatanadilok, Somkid; Veenin, Teera; Yahya, Ahmad Zuhaidi; Nobuchi, Tadashi (Springer, 2014)
Radial variations in vessel features (vessel lumen area and frequency) of four tropical tree species grown in tropical savanna, monsoon, and rainforest climates were investigated to detect indistinct annual rings. Leaf and soil water potentials were measured periodically to show annual variations in water availability and their relationship to radial variations in vessel features. In addition, the accuracy of annual-ring detection was estimated using trees of known age. Radial variations in vessel features showed annual cyclicity in all three sites. The vessel feature that showed clear annual cyclicity was different among the species and sites. Furthermore, the variation pattern of vessel features in the rainforest site tended to be different between two radii within individual trees, implying low synchronicity of wood formation in the wet area. Compared with leaf and soil water potentials, vessel features varied independent of water availability in all species in the rainforest site and most species in the savanna and monsoon sites. The direct effect of low water availability on vessel features was considered only in one species in the savanna and monsoon sites. Nevertheless, the deviation of vessel feature cycles from tree age was similar and reasonably small (mostly within ±10 %) among all sites. These results indicated a circannual rhythm in vessel formation. Thus, vessel feature changes seemed to aid in detecting annual rings in trees throughout wide tropical areas; however, asynchronous wood formation must be considered in dendrochronology, especially in humid tropics.